1997
DOI: 10.1111/j.1348-0421.1997.tb01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella (Branhamella) catarrhalis Adherence to Human Bronchial and Oropharyngeal Cells: The Role of Adherence in Lower Respiratory Tract Infections

Abstract: Abstract:To study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…*P<0.001 mostly investigated by using the cervical cancer derived HeLa subline HEp-2 cell, the HeLa subline Changconjunctival cell and the human lung carcinoma A-549 cell culture model [4, 5, 7-10, 12, 20, 28-30]. In contrast bronchial epithelial cells were rarely used for this purpose [31]. The difficulties associated with the study of the adhesion ability of M. catarrhalis to epithelial cells as a strictly human specific pathogen in vivo have led to the development of in vitro adhesion assays.…”
Section: Discussionmentioning
confidence: 99%
“…*P<0.001 mostly investigated by using the cervical cancer derived HeLa subline HEp-2 cell, the HeLa subline Changconjunctival cell and the human lung carcinoma A-549 cell culture model [4, 5, 7-10, 12, 20, 28-30]. In contrast bronchial epithelial cells were rarely used for this purpose [31]. The difficulties associated with the study of the adhesion ability of M. catarrhalis to epithelial cells as a strictly human specific pathogen in vivo have led to the development of in vitro adhesion assays.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, electron microscopic data revealed that besides pili similar to those of type 4, an additional non-type 4 class of pili exists. Elucidation of the prevalence and role of these pili in the pathogenesis and host response to M. catarrhalis requires further study (171), although preliminary studies have already revealed that fimbriated bacteria bind more efficiently to lower bronchial epithelial cells than nonfimbriated bacteria do (201).…”
Section: Pericellular Structuresmentioning
confidence: 99%
“…For all species of bacteria, their adherence to cells is important for the establishment of infections [1, 2, 3, 4]. We have demonstrated using various pathogens that, for any species, the first step towards lower respiratory tract infections is the adherence of respiratory pathogenic bacteria to the upper respiratory tract, such as the oropharyngeal mucosa, and colonization in that area.…”
Section: Introductionmentioning
confidence: 99%